2009
DOI: 10.1242/dev.026476
|View full text |Cite
|
Sign up to set email alerts
|

LIM homeobox transcription factors integrate signaling events that control three-dimensional limb patterning and growth

Abstract: Vertebrate limb development is controlled by three signaling centers that regulate limb patterning and growth along the proximodistal (PD),anteroposterior (AP) and dorsoventral (DV) limb axes. Coordination of limb development along these three axes is achieved by interactions and feedback loops involving the secreted signaling molecules that mediate the activities of these signaling centers. However, it is unknown how these signaling interactions are processed in the responding cells. We have found that distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 64 publications
(77 reference statements)
10
97
1
Order By: Relevance
“…48 a similar function was suggested for LDB1 in intestinal crypts 49 and for LDB1, 50 and LHX2, 51 in hematopoiesis. specifically, in hematopoiesis, LDB1 has a critical role in the maintenance of fetal and adult hematopoietic stem cells and of cells downstream of them in the erythroid lineage.…”
Section: Modularity Of Chip/ldb Transcription Complexes Regulates Celsupporting
confidence: 65%
“…48 a similar function was suggested for LDB1 in intestinal crypts 49 and for LDB1, 50 and LHX2, 51 in hematopoiesis. specifically, in hematopoiesis, LDB1 has a critical role in the maintenance of fetal and adult hematopoietic stem cells and of cells downstream of them in the erythroid lineage.…”
Section: Modularity Of Chip/ldb Transcription Complexes Regulates Celsupporting
confidence: 65%
“…Second, as mentioned above, a rich field of embryonic limb development has detailed the relationship between transcription factors and AP skeletal patterning (Qu et al, 1997;CharitĂ© et al, 2000;Fernandez-Teran et al, 2000;ZĂĄkĂĄny et al, 2004;Tzchori et al, 2009;Galli et al, 2010;Sheth et al, 2012). Third, our dataset revealed many examples of developmental transcription factors with expression differences along the AP axis.…”
Section: Research Articlementioning
confidence: 56%
“…; *P<0.05, **P<0.005, Student's t-test. confirmed restriction of hand2 to posterior fin rays, and also verified region-specific expression for eight other transcription factor genes: alx4a, lhx9, id4, pax9, tbx2a, hoxc8a, hoxd11a and hoxd13a. Six of these eight transcription factors have roles in AP patterning during limb or fin development (Qu et al, 1997;Harrelson et al, 2004;ZĂĄkĂĄny et al, 2004;McGlinn et al, 2005;Tzchori et al, 2009), whereas id4 has been implicated in bone homeostasis (Tokuzawa et al, 2010). The anterior expression of the Hoxc genes has been described during pectoral fin development (Molven et al, 1990), and HOXC8 has specifically been shown to be expressed in the anterior region of developing chick wings (Nelson et al, 1996).…”
Section: Research Articlementioning
confidence: 99%
“…2001). The conditional mutation of Ldb1 was induced on a background of Ldb2 deficiency to preclude any possible compensation for Ldb1 loss by Ldb2 (Tzchori et al, 2009;Narkis et al, 2012). Ldb1 loxP/loxP ;Ldb2 −/− embryos exhibited a normal retinal phenotype, and thus were used as controls (Fig.…”
Section: Ldb1 Is Expressed In Retinal Progenitors and Is Maintained Imentioning
confidence: 99%
“…Genetic and molecular studies conducted on Ldb1 and Ldb2 have revealed functional redundancy between the two factors (Tzchori et al, 2009;Narkis et al, 2012). To determine directly the potential for Ldb2 to compensate for Ldb1 deficiency during retinal development, we analyzed the retinal phenotype of embryos deficient in Ldb1 in which Ldb2 remained intact (Ldb1 loxP/loxP ; α-Cre).…”
Section: Ldb2 Is Sufficient To Sustain the Rpc Pool And Müller Glia mentioning
confidence: 99%